Comparative Assessment of Fetal Malnutrition by Anthropometry and CAN Score with associated maternal factors in Sub-District hospital of Uttarakhand - Dr. Mamta Nikhurpa; Dr. Vinita Nikhurpa; Dr. Sandeep Pangty (Pediatric Review: International Journal of Pediatric Research, 2021)
Introduction: Fetal malnutrition is an important contributor to perinatal mortality and morbidity. This study was aimed to assess the nutritional status of the newborn at birth using Clinical Assessment of Nutrition (CAN score) and compare it with other conventional anthropometric indices. In addition to studying maternal variables associated with fetal malnutrition.Material and Methods: This prospective study was conducted at Sub-District hospital, Uttarakhand for a 3-month duration from June 2020 to August 2020. Total 765 term, singleton newborn without major congenital malformation or comorbidities were included in the study. Anthropometric indices and CAN score were assessed and compared.Results: The incidence of fetal malnutrition was 17.39% using the CAN score. Fetal malnutrition was detected in 133(17.3%), 65(8.5%), 141(18.4%), 91(11.8%), 85(11.1%) of newborn using CAN score, PI, Gestational age, BMI, and MAC/HC respectively. Out of clinically malnourished babies identified by CAN score, PI, gestational age, BMI and MAC/HC identified 49.23% (32), 76.6% (108), 56.04%(51), 49.41%(42) as fetal malnutrition. BMI has the highest sensitivity and diagnostic accuracy for detecting fetal malnutrition. Maternal variables associated with FM include early maternal age during conception 81.4% (623), primigravida 33.1% (112), anemia (21%), irregular antenatal checkups (40%) and concurrent illnesses (PIH, urinary tract infection, heart disease, renal disease, vascular disease) (50.9%).Conclusion: CAN score is a simple, handy and cost-effective tool to identify FM. Using BMI with CAN score can serve for screening FM. Among maternal variables, primigravida (33.1), anemia (21.5%), irregular antenatal checkup (40.25%), Concurrent medical illnesses (50.96%) is strongly associated with FM. Maternal age is not statistically significant.